2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31194
|View full text |Cite
|
Sign up to set email alerts
|

Using A Fun Six Sigma Project to Teach Quality Concepts, Tools, and Techniques

Abstract: Research has shown that students learn better if they are engaged in, and motivated to struggle with, their own learning [5]. For this reason, if no other, students appear to learn better if they work cooperatively in small groups to solve problems. Furthermore, learning quality engineering concepts, such as variation, using traditional methods can be challenging for many college students with no prior background. It makes it even more challenging when methods such as statistical process control, process capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Feedback received from a previous research study, where a process simulator was used, indicated that students were interested in real processes to work on and improve [19]. For time constraints and lack of manufacturing companies close to campus, opportunities for projects were identified in laboratories utilized for teaching plastics technology as well as additive manufacturing using a 3-D Printer.…”
Section: Project Detailsmentioning
confidence: 99%
“…Feedback received from a previous research study, where a process simulator was used, indicated that students were interested in real processes to work on and improve [19]. For time constraints and lack of manufacturing companies close to campus, opportunities for projects were identified in laboratories utilized for teaching plastics technology as well as additive manufacturing using a 3-D Printer.…”
Section: Project Detailsmentioning
confidence: 99%